Community utilisation and satisfaction with the community-based health planning and services initiative in Ghana: a comparative study in two system learning districts of the CHPS+ project - Margaret Kweku; Hubert Amu; Martin Adjuik; Fortress Yayra Aku; Emmanuel Manu; Elvis Enowbeyang Tarkang; Joyce Komesuor; Geoffrey Adebayor Asalu; Norbert Ndaah Amuna; Laud Ampomah Boateng; Justine Sefakor Alornyo; Roland Glover; et al. (BMC, 2020)
Abstract Background To strengthen the implementation of the Community-based Health Planning and Services (CHPS) programme which is Ghana's key primary health care delivery strategy, the CHPS+ Project was initiated in 2017. We examined community utilisation and satisfaction with CHPS services in two System Learning Districts (SLDs) of the project. Methods This community-based descriptive study was conducted in the Nkwanta South Municipality and Central Tongu District of Ghana. Data were collected from 1008 adults and analysed using frequency, percentage, chi-square, and logistic regression models. Results While the level of utilisation of CHPS services was 65.2%, satisfaction was 46.1%. Utilisation was 76.7% in Nkwanta South and 53.8% in Central Tongu. Satisfaction was also 55.2% in Nkwanta South and 37.1% in Central Tongu. Community members in Nkwanta South were more likely to utilise (AOR = 3.17, 95%CI = 3.98-9.76) and be satisfied (AOR = 2.77, 95%CI = 1.56-4.90) with CHPS services than those in Central Tongu. Females were more likely to utilise (AOR = 1.75, 95%CI = 1.27-2.39) but less likely to be satisfied [AOR = 0.47, 95%CI = 0.25-0.90] with CHPS services than males. Even though subscription to the National Health Insurance Scheme (NHIS) was just 46.3%, NHIS subscribers were more likely to utilise (AOR = 1.51, 95%CI = 1.22-2.03) and be satisfied (AOR = 1.45, 95%CI = 0.53-1.68) with CHPS services than non-subscribers. Conclusion Ghana may not be able to achieve the goal of universal health coverage (UHC) by the year 2030 if current levels of utilisation and satisfaction with CHPS services persist. To accelerate progress towards the achievement of UHC with CHPS as the vehicle through which primary health care is delivered, there should be increased public education by the Ghana Health Service (GHS) on the CHPS concept to increase utilisation. Service quality should also be improved by the GHS and other stakeholders in Ghana's health industry to increase satisfaction with CHPS services. The GHS and the National Health Insurance Authority (NHIA) should also institute innovative strategies to increase subscription to the NHIS since it has implications for CHPS service utilisation and satisfaction.